Objects of marketing in student sports - Gorelikov, Valery A. (Физическое воспитание и студенческий спорт, 2023)
The article analyzes the main objects of marketing in Russian student sports, examines the opportunities for marketing in university sports– international sporting events and sports organizations that create and earn from their marketing products. The relevance of this study is justified by the need to find new sources of funding for the development of university sports in Russia. The objective is to identify existing marketing markets, marketing objects and marketing products in university sports, assess the potential for their implementation and leverage of additional financing. Based on the results of the research, we have identified marketing objects in university sports, segmented markets and studied marketing opportunities for different objects, opportunities and options for realizing the marketing potential of university sports. Currently, university sports in Russia has all the attributes of a developing marketing market – it creates and offers marketing products, works with interested audiences, and has clearly defined marketing objects in the form of sports events, student sports leagues, student sports clubs, student athletes. The market has positive potential for further growth and increase in extra-budgetary revenues of student sports organizations.